Перекладацькі трансформації у процесі відтворення емоційно-оцінної лексики в аудіовізуальному перекладі серіалу «Бріджертони» - Mykytiuk, Iryna; Atitian, Andriana ("Молодий вчений", 2021)
The topicality of the presented article is stipulated by an active interest of modern linguists in the issues of audiovisual translation investigation and emotional evaluative vocabulary rendering as the number of serials in English is constantly rising and the necessity for their adequate translation is continuously increasing. The novelty of our research lies in the fact that an attempt to analyze peculiar techniques of rendering emotional evaluative vocabulary used in a popular Netflix drama series Bridgerton (2020) has been made for the first time. The tasks of the given article are to define audiovisual translation and to analyze translation transformations used in the process of rendering emotional evaluative vocabulary in audiovisual translation of the Bridgerton series. The investigation is based on 739 emotional evaluative lexemes singled out from 8 episodes of Season 1 Netflix drama series Bridgerton (2020) and their translations into Ukrainian by HDrezka Studio. The findings obtained in the result of quantitative and contrastive analyses allow us to conclude that in the course of audiovisual translation of emotional evaluative vocabulary in the Bridgerton series, various translation transformations have been employed. The key one is transposition which makes up 60% of all the transformations. Next in quantity is omission which comprises 28%, followed by replacement / permutation (9,2%) and addition (2,8%). Within transposition (60%) grammatical transposition prevails (22,2%); compensation makes up 21,7%, lexical transposition – 8,7%, antonymic translation – 7,4%. This may be explained by the necessity to ensure the analogous effect from the translation as is meant by the original audiovisual text or product, as well as to avoid redundancy. Furthermore, the translator’s choice is influenced by both linguistic (analytical type of English and synthetical one of Ukrainian) and extralinguistic factors, as well as other limitations such as timing and preservation of articulation. The prospects of further research may be connected with investigation of gender aspect of translation transformations in audiovisual translation of the drama series Bridgerton or the study of techniques for rendering emotional evaluative lexis in another audiovisual or printed text.
Keywords: аудіовізуальний переклад; емоційно-оцінна лексика; перекладацькі трансформації; таймінг